Mobility Management Incorporating Pattern Recognition in the Handoff Decision - Kwong, C.F.; Lee, S.W.; Sim, M.L. (IEEE, 2009)
In the age of global communications, heterogeneous networks are seen to be the best choice of strategy to ensure continuous and uninterruptible services. This will allow mobile terminal to stay in connection even they are migrating into different segment coverage through the handoff process. In the quest for efficient handoff especially in the heterogeneous environment, various techniques of handoff decision making have been used. This paper will discuss different techniques in the traditional handover decision algorithm and explore the method of handoff decision using pattern recognition method, mainly the Adaptive Network Fuzzy Inference System (ANFIS). The paper will also present results simulated in an experiment, and comparison between different handoff algorithms with respect to ANFIS.